Antiepileptogenic and Neuroprotective Effects of Pergularia daemia on Pilocarpine Model of Epilepsy - Kandeda, Antoine K.; Taiwe, Germain S.; Moto, Fleur C. O.; Ngoupaye, Gwladys T.; Nkantchoua, Gisele C. N.; Njapdounke, Jacqueline S. K.; Omam, Jean P. O.; Pale, Simon; Kouemou, Nadege; Ngo Bum, Elisabeth (Frontiers in Pharmacology, 2017)
In this study, we investigated antiepileptogenic and neuroprotective effects of the aqueous extract of Pergularia daemia roots (PDR) using in vivo and in vitro experimental models. In in vivo studies, status epilepticus caused by pilocarpine injection triggers epileptogenesis which evolves during about 1–2 weeks. After 2 h of status epilepticus, mice were treated during the epileptogenesis period for 7 days with sodium valproate and vitamin C (standards which demonstrated to alter epileptogenesis), or Pergularia daemia. The animals were then, 1 week after status epilepticus, challenged with acute pentylenetetrazole (PTZ) administration to test behaviorally the susceptibility to a convulsant agent of animals treated or not with the plan extract. Memory was assessed after PTZ administration in the elevated plus maze and T-maze paradigms at 24 and 48 h. Antioxidant and acetylcholinesterase activities were determined in the hippocampus after sacrifice, in vitro studies were conducted using embryonic rat primary cortical cultures exposed to L-glutamate. Cell survival rate was measured and apoptotic and necrotic cell death determined. The results showed that chronic oral administration of PDR significantly and dose-dependently increased the latency to myoclonic jerks, clonic seizures and generalized tonic–clonic seizures, and the seizure score. In addition, PDR at all doses (from 4.9 to 49 mg/kg) significantly decreased the initial and retention transfer latencies in the elevated plus maze. Interestingly PDR at the same doses significantly increased the time spent and the number of entries in T-maze novel arm. PDR significantly increased the activities of acetylcholinesterase and antioxidant enzymes superoxide dismutase, catalase, and total glutathione and proteins, and decreased malondialdehyde level. Furthermore, PDR increased viability rate of primary cortical neurons after L-glutamate-induced excitotoxicity, in a dose dependent manner. Altogether these results suggest that PDR has antiepileptogenic and neuroprotective effects, which could be mediated by antioxidant and antiapoptotic activities.